TEACHING NARRATIVE READING BY USING CHARACTER QUOTES STRATEGY TO THE ELEVENTH GRADE STUDENTS OF MAN 1 PALEMBANG - Novinda Bersa Kareni (Edukasi, 2016)
The objectives of this study are to find out whether or not there is a significant improvement before and after the treatment on the eleventh grade students’ reading comprehension scores of MAN 1 Palembang by using Character Quotes strategy and to find out whether or not there is a significant difference on the eleventh grade students’ reading comprehension scores of MAN 1 Palembang between the students who are taught by using Character Quotes strategy and those who are not. In this study, the researcher used Quasi Experimental Design using pretest-posttest nonequivalent groups design. Purposive sampling was used, where 30 students belonged to experimental group and 30 students belonged to control group. In collecting the data, test was used. The test was given twice to both experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05 and t-value 11.399 was higher than t-table with df=29 (2.0452).  The result of p-output from independent sample t-test was 0.001 which was lower that 0.05 and the t-value 3.465 was higher than t-table with df=58 (2.0017). It means that teaching narrative reading by using Character Quotes strategy had significant effect on the students’ reading comprehension scores.